PERAN ORANG TUA DAN GURU DALAM UPAYA PENCEGAHAN KEKERASAN SEKSUAL (ABORSI) PADA REMAJA - Tb. Akbar Agung Tunjung Putih; Indra Saripudin; Ismail; Azhar Savero Sukma (Jurnal Riset Multidisiplin Edukasi, 2026)
This community service activity aims to increase the understanding of parents and teachers in preventing sexual violence and abortion among adolescents at SMKN 7 Pandeglang. Sexual violence and abortion among adolescents are increasingly alarming social problems in Indonesia, requiring active roles from family and school environments as the first line of defense. The activity was carried out through socialization, interactive discussions, and material briefings to 50 student and teachers. The results showed that participants experienced an increase in knowledge and awareness regarding signs of sexual violence, effective communication with adolescents, and preventive measures applicable at home and school. This program is expected to strengthen the synergy between parents and teachers as the frontline guardians of adolescent protection.